Introducing Hijaiyah Letter and Training in Writing Arabic Letters for Students of the Islamic Economics Study Program - Tira Nur Fitria (UPT Publikasi dan Penerbitan Universitas San Pedro, 2023)
This activity introduces hijaiyah letters and teaches how to write Arabic for non-Arabic study program students in ITB AAS Indonesia. This activity is held on 22 February 2023 in offline meetings, Zoom Meetings, and Live Streaming on YouTube. There are 20 students in the Islamic Economics Study Program in the 2nd semester involved in this activity. This activity is carried out through demonstrations and discussions. In the implementation of this activity, the speaker introduces Hijaiyah Letter and Harakat (Arabic vowel) to grow students' attention to the importance of learning Hijaiyah and writing Arabic. After explaining, the speaker gives assignments. The speaker gives two assignments for students to write hijaiyah letters and Arabic, especially Surah Yasin. The purpose of giving these assignments is to help the students master the rule of writing hijaiyah and can write Surah Yasin correctly. Based on the students’ writing, shows that students consider the rule of writing hijaiyah letters correctly and can write Arabic well. Writing hijaiyah letters has a higher level of difficulty compared to Latin letters because almost all of the letters can change shape based on the position of the letter when it is in the front, middle, or end of the word.